PADANAN BENTUK ~TAI DALAM BAHASA INDONESIA - Sherlyana Safira; Arza Aibonotika; Yenny Aristia Nasution (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: In Japanese the suffix ~tai is used to express the meaning of desire, while in Indonesian it is often paired with ‘ingin’ and ‘mau’. However, when translating, the translators assume that the form of ~tai in various forms is influenced by the attitude of the translator which is based on pragmatic aspects rather than morphological and syntactic problems. Therefore, in this study, we will see how the equivalent form of ~tai is in Indonesian. This study used descriptive qualitative method. The data of this study used primary data from the Japanese novel Botchan (1978) by Natsume Sōseki and its Indonesian translation as a comparison. The results indicated that the meaning of the suffix ~tai can express 'desire' which is characterized by the use of ‘ingin’, ‘kepingin’, ‘keinginan’, ‘mau’, ‘menyesal’, ‘berharap’ ; ‘willingness' with the use of ‘mau’, ‘ingin’, ‘berminat’, ‘rela’ ; and 'intention' which can be equated with the use of ‘mau’ and ‘untuk’.Key Words: ~Tai, Modality